2018
DOI: 10.1063/1.5055862
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of crystallization of solid ethanol

Abstract: Experimental studies of the kinetics of phase transitions of C2H5OH ethyl alcohol samples from amorphous to crystalline phase demonstrated that their transition rate and energy characteristics strongly depend on the size and composition of the samples (rectified alcohol, absolute alcohol). Almost all bulk amorphous samples of rectified alcohol that were several millimeters in size crystallized into the monoclinic phase within few hours at a temperature of T ∼ 125 K, while in amorphous nanocluster samples consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This hypothesis is confirmed by Efimov et al, 27 who studied the kinetics of phase transition of solid ethanol from the amorphous to the crystalline phase and found the size effect in the rate and activation energy of this transition. They showed that bulk amorphous samples of solid alcohol that were several millimeters in size crystallized into the monoclinic phase within several hours at approximately 125 K, while “in amorphous nanocluster samples consisting of clusters of the order of tens nanometers in size, a similar transition was observed”, even at 110 K. However, this also contradicts our data, since we did not detect the phase transition upon warming the amorphous film grown on platinum at 80 K by exposing to 300 L of ethanol even at 120 K for 2 h. In this case, the average thickness of the solid ethanol film was approximately 30 ML or 18 nm.…”
Section: Resultssupporting
confidence: 61%
“…This hypothesis is confirmed by Efimov et al, 27 who studied the kinetics of phase transition of solid ethanol from the amorphous to the crystalline phase and found the size effect in the rate and activation energy of this transition. They showed that bulk amorphous samples of solid alcohol that were several millimeters in size crystallized into the monoclinic phase within several hours at approximately 125 K, while “in amorphous nanocluster samples consisting of clusters of the order of tens nanometers in size, a similar transition was observed”, even at 110 K. However, this also contradicts our data, since we did not detect the phase transition upon warming the amorphous film grown on platinum at 80 K by exposing to 300 L of ethanol even at 120 K for 2 h. In this case, the average thickness of the solid ethanol film was approximately 30 ML or 18 nm.…”
Section: Resultssupporting
confidence: 61%
“…Ethanol is known for the presence of different solid forms depending on the temperature and thermal process used. For the bulk, rapid cooling to a temperature lower than 100 K results in an amorphous solid, whereas a rotator phase and an orientational glass may be produced by moderate cooling of the liquid. The monoclinic crystalline structure can be readily obtained at a temperature close to melting or by annealing of the amorphous solid.…”
Section: Introductionmentioning
confidence: 99%